Retracing the roots of educational technology in the Philippines - Rabin, Rhea Christina U. (2007)
Unfolding the history of educational technology is an attempt to construct the meaning, function, root and development of EDTECH in the Philippines. This paper provided historical data of the various aspects of EDTECH such as indigenous technology, audio-visual and media technology, psychological approaches, instructional system design, and information technology. Historical research method was employed. The study also revealed how Filipinos tried to solve the problem of access and quality education using EDTECH. Much still needs to be done to maximize the full potential of EDTECH. The historical data could be used to empower educators in making decisions on the use of EDTECH in the future.